Influence of availability of shade on testicular characteristics of Santa Ines rams - doi: 10.4025/actascianimsci.v35i.18479 - Sônia Martins Teodoro; Alfredo Manuel Franco Pereira; José Dantas Gusmão Filho; Jadir Nogueira da Silva (Acta Scientiarum. Animal Sciences, 2013)
The purpose of this study was to evaluate the effects of availability of artificial shading ontesticular and seminal characteristics of Santa Ines crossbred rams. Twelve 8 month old rams at 38.1 ± 5.2 kgaverage weight, were used in a total random design with two treatments: areas with and without available artificialshading (black polyethylene mesh screen for a 50% reduction of solar radiation). The scrotal circumference,scrotal length, scrotal volume, rectal temperature and scrotal temperature were measured twice a week. Also abiweekly analysis of the semen was carried out, measuring the volume and spermatic concentration as well as thepercentage of normal spermatozoa. The results show that available shading provided for lower scrotaltemperatures and higher sperm concentration, without influencing the scrotal volume and the percentage ofnormal spermatozoa. The testicular measures, such as the scrotal circumference and length were higher in therams that were subjected to the no available shading treatment. The absence of differences, in some of theanalyzed variables, between the two treatments, with and without available shading, could be due to highadaptability of the animals.